THE EFFECTIVENESS OF THE IMPLEMENTATION OF DIGITALIZATION THROUGH WEB E-COMMERCE IN JANTI BUMDES TO INCREASE ECONOMIC COMPETITIVENESS - Adilita, Vara Riya; Rodiyah, Isnaini (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the effectiveness of digitalization through the e-commerce platform of BUMDes Janti, Waru District, Sidoarjo Regency, in enhancing the economic competitiveness of the village, particularly by increasing market access and income for local MSMEs. Method: A descriptive qualitative approach with a case study design was employed, using primary data from in-depth interviews with BUMDes managers and MSME actors, as well as direct observation of the digitalekonomijanti.co.id platform. Secondary data were drawn from official BUMDes documentation, financial reports, journals, and related articles. Results: The findings indicate that digitalization via e-commerce has effectively encouraged MSME participation, broadened marketing reach, and improved transaction efficiency, though challenges remain in digital literacy and internet infrastructure. Moreover, BUMDes plays a more significant role as a facilitator, providing infrastructure and technological support, rather than as the primary business operator. Novelty: The study highlights that the success of digitalization is not solely determined by BUMDes’ direct management but also by its capacity to act as a facilitator that maps local potential, fosters social networks, and adapts technology to community needs, offering an alternative model for digital economic development rooted in local wisdom.